Efecto de cuatro dosis de gallinaza en el cultivo de Maracuyá (Passiflora Edulis) en suelos ácidos, Aucaloma – Lamas – Perú - Tuanama Escudero, José Luis (2013)
The aim of the research was to determine the effect of using different doses of composting manure on growth, development and profitability performance of passion fruit cultivation. He settled in the Aucaloma founded the National University of San Martin, located 700 msnmm under the completely randomized design with four doses (3000 , 5000, 7000, 9000 kg / ha of manure ) compared with absolute control , we evaluated height plant , number of leaves , number, weight and fruit diameter , fruit wastage , and economic analysis . The application of manure has improved in redeeming fruit passionfruit , observed performance increase upward as the dose was increased , doses of 7000 and 9000 kg / ha of manure improved plant height , number of leaves , number , weight , diameter and yield harvested fruits , as a result yields are obtained 14 390 17 270 kg / ha of fruit , with a cost -benefit ratio ranging from 0.55 to 0.73 cents again sun sun each invested and benefit cost ratio of 54.62 % to 72.76 %.